Culture, and its Psychotherapeutic Influences on Emotions, Cognitions, and Motivations - Haq, Farah (International Journal of Psychology, 2025)
Purpose: This study explores the psychotherapeutic influences of culture on emotions, cognitions, and motivations. It emphasizes culture's role in shaping individual identity, well-being, and behavioral outcomes. Methodology: The research involves a literature review focusing on cultural definitions, emotional development, motivational drivers, and their therapeutic applications. Findings: Key findings reveal the dynamic and evolving nature of culture, its foundational role in shaping cognition and identity, and its impact on emotional and motivational processes. The study underscores the necessity of culturally competent psychotherapy to address diverse sociocultural challenges, foster therapeutic connections, and promote mental health. Unique Contribution to Theory, Practice and Policy: The study highlights the importance of understanding culture as a critical clinical discipline to better address its influence on individual and collective experiences.